2015
DOI: 10.1108/ijlls-09-2014-0034
|View full text |Cite
|
Sign up to set email alerts
|

Lesson study and the development of teacher’s competences

Abstract: Purpose – The purpose of this paper is to show, from a theoretical point of view, the promising relationship between the processes generated by Lesson Studies (LS) and the development of practical thinking in in-service teacher training, derived from two pieces of research. Design/methodology/approach – The authors propose broadening the focus of LS in order to not only improve the “lesson” or “teaching” – in short, practice – but also t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 28 publications
1
13
0
4
Order By: Relevance
“…The data from this study revealed that the EFL teachers in the Basque Country appreciated LS's iterative dynamic, its focus on collaborative inquiry, professional dialogue and reflection in an authentic classroom. Overall, the data corroborate with the literature on the affordances of LS methodology for teacher professional development in Spain, enhancing teachers' professional competences and practical thinking (Peña Trapero, 2013;Soto G omez et al, 2015). Thus, we suggest that LS could be considered an effective framework for building professional learning communities in the schools of the Basque Country, which might stir positive changes in teaching practice, increase the quality of teaching and thus, positively impact students' achievements and well-being.…”
Section: Ijlls 103supporting
confidence: 86%
See 1 more Smart Citation
“…The data from this study revealed that the EFL teachers in the Basque Country appreciated LS's iterative dynamic, its focus on collaborative inquiry, professional dialogue and reflection in an authentic classroom. Overall, the data corroborate with the literature on the affordances of LS methodology for teacher professional development in Spain, enhancing teachers' professional competences and practical thinking (Peña Trapero, 2013;Soto G omez et al, 2015). Thus, we suggest that LS could be considered an effective framework for building professional learning communities in the schools of the Basque Country, which might stir positive changes in teaching practice, increase the quality of teaching and thus, positively impact students' achievements and well-being.…”
Section: Ijlls 103supporting
confidence: 86%
“…In Spain, the employment of the LS methodology for enhancing teachers' professional competencies and practical thinking has a long tradition in Malaga and the region of Andaluc ıa (Peña Trapero, 2013;Soto G omez et al, 2015). Nevertheless, there is no literature available in the context of the Basque Autonomous Community (BAC), where this study is set.…”
Section: Context and Participantsmentioning
confidence: 99%
“…It is also essential for the curriculum to specialize in pedagogical areas according to the technical skills. Gómez, Núñez, & Gómez (2015) suggested that a specific design in-service programme would lead to the reconstruction of components that results in unaffected to unwanted practical knowledge. By being specialized, TVET Teacher Education programme will produce TVET teacher who is an expert in the related skill.…”
Section: Resultsmentioning
confidence: 99%
“…Not only that, the curriculum must also be embedded with values to produce TVET teachers that are in line with the National Education Framework. Values may provide guidelines in formulating personal as well as collective goals or aims (Gómez et al, 2015). Several experts mentioned the dynamics of curriculum as a criterion as seen in the quotations from interview transcripts below:…”
Section: Resultsmentioning
confidence: 99%
“…Se requiere desarrollar cualidades cognitivas y socioemocionales de nivel superior, un pensamiento práctico informado, autónomo y creativo. Es decir, el desarrollo singular y holístico en cada individuo de las dimensiones sustanciales de su personalidad, las cualidades, capacidades o competencias como sistemas complejos de comprensión, autoorganización y actuación, que incluyen al mismo nivel y con la misma relevancia, conocimientos, habilidades, emociones, actitudes y valores como sus componentes esenciales (Korthagen, 2017;Pérez Gómez, 2012Soto et al, 2015).…”
Section: Promover La Experiencia Educativa Relevante Y Reflexivaunclassified